Integrin β1 activity controls colony morphology during human pluripotent stem cell state transitions - Taskinen, Maria E.; Pasquier, Nicolas; Stubb, Aki; Joshi, Shreya; Chastney, Megan R.; Rasila, Paula; Vahlman, Sonja; Sokka, Joonas; Lönnberg, Tapio; Mikkola, Lea; Trokovic, Ras; Ivaska, Johanna (Elsevier BV, 2025)
Integrin β1-mediated adhesion is dispensable in early mouse embryogenesis (pre-implantation) but indispensable post-implantation, suggesting distinct roles for β1-integrin-mediated adhesions in the naive (pre-implantation) versus primed (post-implantation) pluripotent stem cells (PSCs). We investigated the role of integrin β1 in regulating naive-like and primed human induced PSC (hiPSC) states. We find that integrin β1 is active in both in vitro. In primed hiPSCs, integrin β1 inhibition induces naive-like colony features, reduces actomyosin contraction and extracellular signal-regulated kinase (ERK) activity, and alters gene expression, indicative of more naive-like features. These resemble the dramatic reorganization of the colony morphology, actin cytoskeleton, and adhesions upon chemical reversion from primed to naive states of pluripotency. Importantly, functional and single-cell transcriptomics analyses demonstrate that integrin β1 inhibition attenuates colony morphology transitions in cells exiting naive pluripotency. These data reveal unprecedented integrin-dependent regulation of PSC states and demonstrate how integrin inhibitors may help to fine-tune hiPSC function and properties in vitro.